BANK DIVERSIFICATION & THE SYSTEMATIC RISK OF EQUITY PORTFOLIO - Alshomaly, Ibrahim (European Scientific Journal, ESJ, 2014)
The paper aims at identifying the potentials of decreasing the systematic risks of banking equity portfolio through changes in the diversification nature of banks activities. We analyzed the financial statements of (13) Jordanian banks on parallelism with market index of Amman stock exchange (ASE) for the period (2006-2012). We used Herfindahl Hirschmann index (HHI) to measure the diversification degree of revenue, credit, and deposits activities.The study concluded that (a) stock market has evaluated the changes in revenue diversification more efficiently than changes in the structure of credit or deposits regarding the systematic risks of bank equity portfolio.(b) The concentration of interest income in the bank’s revenue portfolio was high and was positively correlated with changes in the systematic risks of trading. (c) The Jordanian banks were more diversified regarding credit and deposit activities, but this diversification was not evaluated by market. And finally, the study showed that there is a decline in the value of systemic risk over the period of study.